2|x-3|+(-12-6)=0
2|x-3| = 0 - (-12-6)
2|x-3| = 0 + (12+6)
2|x-3|= 18
|x-3| = 18 : 2
|x-3| = 9
x-3=9
x=9+3
x=12
Vậy: x=12
Cái trước mình viết thiếu, xin lỗi bạn
2|x-3|+(-12-6)=0
2|x-3| = 0 - (-12-6)
2|x-3| = 0 + (12+6)
2|x-3| = 18
|x-3| = 18 : 2
|x-3| = 9
TH1: TH2:
x - 3 = 9 x - 3 = -9
x = 9 + 3 x = (-9)+3
x = 12 x = -6
Vậy: x = 12 hoặc x = -6
Theo đề ta có:
2|x-3|+(-12-6)=0
=> \(\left[{}\begin{matrix}\text{2|x-3|+(-18)=0}\\\Rightarrow2\left|x-3\right|=0-\left(-18\right)\\\Rightarrow2\left|x-3\right|=0+18\\\Rightarrow2\left|x-3\right|=18\end{matrix}\right.\)
=> \(\left[{}\begin{matrix}\Rightarrow\left|x-3\right|=\dfrac{18}{2}\\\Rightarrow\left|x-3\right|=9\\\end{matrix}\right.\)
=> \(\left[{}\begin{matrix}x-3=9\\x-3=-9\end{matrix}\right.\)
=> \(\left[{}\begin{matrix}x=9+3\\x=-9+3\end{matrix}\right.\)
=> \(\left[{}\begin{matrix}x=12\\x=-6\end{matrix}\right.\)